1995
DOI: 10.1038/nm1095-1082
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to adverse consequences of anti–cholinesterases in ‘atypical’ BCHE carriers

Abstract: Normal butyrylcholinesterase (BuChE), but not several of its common genetic variants, serves as a scavenger for certain anti-cholinesterases (anti-ChEs). Consideration of this phenomenon becomes urgent in view of the large-scale prophylactic use of the anti-ChE, pyridostigmine, during the 1991 Persian Gulf War, in anticipation of nerve gas attack and of the anti-ChE, tacrine, for improving residual cholinergic neurotransmission in Alzheimer's disease patients. Adverse symptoms were reported for subjects in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 22 publications
3
48
0
2
Order By: Relevance
“…Of the numerous BCHE mutations, we genotyped the D70G substitution yielding the ''atypical'' BChE variant, with enzymatic activity 30% lower than the wild-type enzyme (34). Homozygous carriers of this polymorphism display extreme anxiety after exposure to anti-AChEs (35). Genotypes at all seven positions did not deviate from Hardy-Weinberg equilibrium expectations.…”
Section: Resultsmentioning
confidence: 99%
“…Of the numerous BCHE mutations, we genotyped the D70G substitution yielding the ''atypical'' BChE variant, with enzymatic activity 30% lower than the wild-type enzyme (34). Homozygous carriers of this polymorphism display extreme anxiety after exposure to anti-AChEs (35). Genotypes at all seven positions did not deviate from Hardy-Weinberg equilibrium expectations.…”
Section: Resultsmentioning
confidence: 99%
“…In human blood, however, BChE, at 50 nM, is 3-fold more abundant than AChE (32). This difference might be physiologically important, because the A␤ fibril-formation process likely involves continuous communication between the brain and the circulation (33) and because BChE interacts with A␤ in the soluble phase.…”
Section: Discussionmentioning
confidence: 99%
“…Organophosphorus poisoning and anaesthesia ................................................................................................................................................................................................................................................ Normal cholinesterase, but not several of its common genetic variants, serves as a scavenger for certain anticholinesterases such as OP compounds. Loewenstein-Lichtenstein et al [118] reported an Israeli soldier homozygous for atypical cholinesterase who suffered severe symptoms following pyridostigmine prophylaxis during the Gulf War. His cholinesterase was far more sensitive than normal cholinesterase to inhibition by anticholinesterases.…”
Section: Biochemistrymentioning
confidence: 99%